Treatment of hyperfunctioning thyroid nodules with ultrasound guided percutanous ethanol injection - 30 months experience - Brkljačić, Boris (Radiology and oncology (Ljubljana), 1999)
Background. Our technique of performing percutaneous ethanol injection (PEI) and results after 30 months are presented and compared with results from the literature. Material and methods. PEI was performed in 40 patients (37 female,3 male, age range 28-76 years); in 35 cases, there was a solitary, scintigraphically "hot" nodule, and in 5 cases a toxic nodulargoiter was found. The volume of treated nodules was in the range from 2.5 to 38 ccm (meanvolume 20.7+-14.1 ccm). Ethanol was injected with the free-hand technique, usually in multiple sessions, with the color and power Doppler ultrasound guidance. The total injected volume of ethanol was 1.5 times the volume of the treated nodule. Results. The procedure was technically successful in 37 patients (92.5%). Pain during injection was observed in all cases, subcutaneous hematoma in 6 cases, and transitory dysphonia in one patient. There were no long-term complications. In 36 patients, the successfulness of the treatment was evaluated after 3-4 months on the basis ofscintigraphy, hormonal status and ultrasonographic findings. A complete and partial cure was achieved in 22 (61.1%) and in 10 patients (278%) of patients,respectively, whereas in 4 patients (11.1 %) the result was unsatisfactory, since only a moderate hormonal remission was observcd after the completion of the procedure. A satisfactory result was observed in 32/36 patients (88.9%). Significant reduction of nodular volume was noted in all cases. A better result was observed in smaller nodules and in cases of autonomous adenomas. No cases of recurrent hyperthyreosis were detected. Conclusions. Percutaneous ethanol injection under ultrasound guidance is an efficient and safe rnethod in the treatment of autonomous thyroid nodules, that enables inactivation of nodules with minimal and/or transitory complications, without permanent or serious complications that can be observedafter radioiodine or surgical therapy.
Keywords: Adenoma; Alcohol, ethyl; Diagnosis; Thyroid neoplasms; Thyroid nodule; Treatment outcome; Ultrasonography